2008
DOI: 10.1016/j.compbiolchem.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Aconitum and Delphinium sp. alkaloids as antagonist modulators of voltage-gated Na+ channels

Abstract: Early pharmacological studies of Aconitum and Delphinium sp. alkaloids suggested that these neurotoxins act at site 2 of voltage-gated Na + channel and allosterically modulate its function. Understanding structural requirements for these compounds to exhibit binding activity at voltagegated Na+ channel has been important in various fields. This paper reports quantum-chemical studies and quantitative structure-activity relationships (QSARs) based on a total of 65 natural alkaloids from two plant species, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Total energy and the energy of the highest occupied molecular orbital represent reaction activity. The energies of frontier molecular orbitals, E HOMO and E LUMO were widely used in developing the QSAR model, for studying the various mechanisms of organic compounds, such as toxicity and degradability [8] . The electrostatic descriptor qH + reflects characteristic of the charge distribution of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Total energy and the energy of the highest occupied molecular orbital represent reaction activity. The energies of frontier molecular orbitals, E HOMO and E LUMO were widely used in developing the QSAR model, for studying the various mechanisms of organic compounds, such as toxicity and degradability [8] . The electrostatic descriptor qH + reflects characteristic of the charge distribution of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…More than 50% of the compounds experimentally tested exhibited clear a blockade of the Ca V 3.2‐mediated T‐type current (i. e. 16 out of the 38 molecules tested were active hits). Rasulev et al . reported quantum‐chemical studies and QSAR analysis for toxicity end‐points on a series of 65 diterpene alkaloids, which comprised blockers and activators of sodium ion channels.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of the compounds experimentally tested exhibited clear a blockade of the Ca V 3.2-mediated T-type current (i. e. 16 out of the 38 molecules tested were active hits). Rasulev et al [33] reported quantum-chemical studies and QSAR analysis for toxicity end-points on a series of 65 diterpene alkaloids, which comprised blockers and activators of sodium ion channels. The authors concluded that the energetic tendency of HOMO-LUMO energy gap helps to distinguish between activators and blockers (where HOMO and LUMO are the energies of highest occupied molecular orbital and lowest unoccupied molecular orbital, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…puberulum and A. sinomontanum (De-Quan and Das, 1983;Mu et al, 2012;Shafikova et al, 2008;Sun et al, 2009a, b, c). Since lappaconitine was extracted, it has exhibited a wide range of biological activities (Ahmad et al, 2008;Dzhakhangirov et al, 2007;Tolstikova et al, 2007Tolstikova et al, , 2009Turabekova et al, 2008); for example, the form of hydrobromide (the compounds of other salt forms are not reported yet) has been widely used in clinical for treatment of neuropathic pain as a non-addictive drug in China (Ou et al, 2011;Wang et al, 2009a, b) and as an antiarrhythmic in Uzbekistan (Yunusov, 2011). However, analgesic effect was hampered due to the low efficiency in clinical (Sun et al, 2011a(Sun et al, , b, 2012(Sun et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%